Growth, Inequality and Poverty Relationships - Almas Heshmati (Institute for the Study of Labor (IZA), 2004)
This paper examines the causal relationship between inequality and a number of macroeconomic variables frequently found in the inequality and growth literature. These include growth, openness, wages, and liberalisation. We review the existing cross-country empirical evidence on the effects of inequality on growth and the extent to which the poorest in society benefit from economic growth. The linkage between growth, redistribution and poverty is also analysed. In the review of literature mainly empirical examples from 1990s are taken. In addition we test the conditional and unconditional relationship between inequality and growth in the post World War II period using WIDER inequality database. Regression results suggest that income inequality is declining over time. Inequality is also declining in growth of income. There is a significant regional heterogeneity in the levels and development over time. The Kuznets hypothesis represents a global U-shape relationship between inequality and growth.
Keywords: F14; D63; C23; O57; O40; 330; growth; openness; income inequality; wage inequality; poverty; indices; Einkommensverteilung; Wirtschaftswachstum; Armut; Kuznets Kurve; Schätzung; Welt